2018
DOI: 10.2741/s500
|View full text |Cite
|
Sign up to set email alerts
|

Microperimetric biofeedback training fundamentals strategies and perspectives

Abstract: Microperimetric biofeedback training (MBFT) is a visual rehabilitative strategy based on fixation stability improvement reinforcing or creating a new preferential fixation locus. The rationale consists in reeducating visual system to a new visual condition, promoting retina-brain transmission, and thus cortical plasticity. The use of MBFT found is major application in visual diseases involving central vision, but later it revealed promising functional outcomes even in myopia, inherited retinal degenerations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…In accordance with the literature, our results also highlight the positive effects of biofeedback on the functional abilities of people with vision impairments. The results of our study confirm the findings of other authors, reporting fixation stability and reading speed as a daily living visual task and improvement for visually impaired subjects with central field loss 18 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the literature, our results also highlight the positive effects of biofeedback on the functional abilities of people with vision impairments. The results of our study confirm the findings of other authors, reporting fixation stability and reading speed as a daily living visual task and improvement for visually impaired subjects with central field loss 18 …”
Section: Discussionsupporting
confidence: 92%
“…The majority of the current techniques involve the use of biofeedback, and one of the most used tools in this area, which supports this rehabilitation method, is the microperimeter. [16][17][18] The microperimeter, in particular MP-3 (Nidek Technologies, Padua, Italy), which consists of a fundus camera and a dedicated personal computer with a specific operating system for the acquisition, analysis, and processing of data, allows structured photo stimulation through biofeedback, dynamic and real-time visualization of the retina to be examined, execution of functional tests of the differential threshold of retinal sensitivity, fixation tests, and retinography. This study aimed to evaluate the effects of two different MP-3 biofeedback strategies on the visual performance of subjects with central vision loss.…”
mentioning
confidence: 99%
“…Biofeedback training (BT) is a compensatory rehabilitation technique that emerged three decades ago and has been used in various fields of medicine, including ophthalmology ( 11 , 12 ). BT is one of the newest and more modern low vision rehabilitation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have researched the bene ts of MBFT and showed promising results. [11][12][13][14] To date, standard practice consensus regarding the required frequency and number of sessions is not applicable. Therefore, this study aimed to examine the impact of microperimetric biofeedback training on visual acuity, near vision acuity, xation stability, and reading rate in patients with AMD.…”
Section: Introductionmentioning
confidence: 99%